A Field Investigation of Solubility and Food Chain Accummulation of Biosolid-Cadmium Across Diverse Soil Types - McLaughlin, M.; Whatmuff, M.; Warne, M.; Heemsbergen, D.; Barry, G.; Bell, M.; Nash, D.; Pritchard, Deborah (CSIRO Publishing, 2006)
Cadmium is a potentially toxic metal that is an unwanted contaminant in urban wastewater biosolids, and has the potential to accumulate through the food chain. This study found that the accumulation of cadmium in wheat grain from application of urban biosolids to soils in Australia was less than cadmium in a water-soluble form. The critical soil cadmium concentration, above which wheat grain would exceed food contaminant limits, could also be simply predicted using the soil pH (acidity) and clay content.